Effect of ethanol extract of Ganoderma lucidum from Tasikmalaya against the growth of Salmonella sp bacteria and some Pathogenic Fungi using the Kirby-Bauer method in vitro - Khusnul Khusnul; Meti Kusmiati; Rianti Nurpalah; I Nyoman Pugeg Aryantha; Tutus Gusdinar Kartawinata (LPPM Universitas Bakti Tunas Husada, 2022)
Ganoderma lucidum (lingzhi) can be used as traditional medicine. This mushroom has many properties, one of which is as an antimicrobial. Antimicrobial functions as antibacterial, antiviral, and antifungal. Lingzhi contains organic alkaloid compounds, flavonoids, and triterpenoids. One of the bacteria that often cause disease in Indonesia is Salmonella sp and several dermatophyte diseases caused by infection with several pathogenic fungi such as Malassezia furfur, Trichophyton rubrum, and Trichophyton mentagrophytes . This study aimed to determine the inhibitory power of Lingzhi from Tasikmalaya ethanol extract against Pathogenic Microorganism. The method used is tested against the anti-microbial used by using the diffusion method using disc paper or Kirby Baure. The analysis showed that the 70% ethanol extract of Lingzhi mushrooms had antibacterial activity against salmonella sp as evidenced by the presence of an average inhibition zone at a concentration of 50% (16,57mm), 60% (18,1mm); 70% (18,55mm), 80% (19.17mm), 90% (21,2mm), and 100% (21,8mm). Inhibitory ability against several pathogenic fungi was able to inhibit at a concentration of 100% with a diameter of Trichophyton rubrum, Trichophyton mentagrophytes and Malassezia furfur with an average diameter of inhibition of 12.9 mm, 9.4 mm, and 6 mm.